Kinerja Penetapan Peraturan Daerah Pada Tahun 2015-2017 di DPRD Kota Palangkaraya - Raden Biroum Bernardianto; Vina Panduwinata (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this study was to describe and analyze the performance of the Regional Parliament of Palangka Raya in carrying out legislative powers and to describe and analyze the constraints that affect the Palangka Raya City DPRD in setting regional regulations. This study uses descriptive qualitative research methods. The types and sources of data chosen by researchers are primary data and secondary data. Data collection techniques used to obtain information are interviews and documentation. The results of the study show that the performance of the Palangka Raya City DPRD (DPRD) in exercising legislative power with the City of Palangka Raya government is quite good. In the period 2015 to 2017, 36 local regulations have been discussed and established. However, if it is reviewed from the proposal initiation, it can be said to be unsatisfactory, because only 9 Regional Regulations are the initiative of the Palangka Raya City DPRD. Factors that influence the performance of the DPRD of Palangka Raya City in setting regional regulations are: Human Resources, Data and Information, and Experience. The condition of Human Resources with an average Bachelor level education (21 out of 30 people) is actually a supporting factor for performance. Given that the basic education is not in line and experience that is still lacking, it becomes an obstacle to support the legislative performance of members of the Palangka Raya City DPRD.